On Fekete-Szegö Problems for Certain Subclasses Defined by q-Derivative. (7th September 2017) - Aldweby, Huda; Darus, Maslina
Abstract : We derive the Fekete-Szegö theorem for new subclasses of analytic functions which are q -analogue of well-known classes introduced before.